2018
DOI: 10.1016/j.ijcard.2017.11.095
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal atrial and ventricular premature contractions with an increased risk of dilated cardiomyopathy caused by a Na v 1.5 gain-of-function mutation (G213D)

Abstract: The Na1.5_G213D mutation is associated with a gain-of-function phenotype, multifocal atrial and ventricular ectopy and dilated cardiomyopathy. Since patients with a MEPPC-like phenotype may specifically benefit from Class-1 antiarrhythmic drugs or amiodarone, clinical identification of this disease entity is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
5
36
0
Order By: Relevance
“…Likewise previously reported in the MEPPC syndrome (Beckermann et al, 2014; Calloe et al, 2018; Laurent et al, 2012; Mann et al, 2012; Nair et al, 2012; ter Bekke et al, 2018; Zakrzewska‐Koperska et al, 2018), our patient presented incessant multifocal polymorphic PVCs originating from the fascicular‐Purkinje system, atrial ectopic beats, and junctional rhythm responsible for DCM and left ventricular dysfunction. Concerning the molecular mechanisms leading to DCM, we can only speculate, like others (Bezzina & Remme, 2008), on a role for altered calcium homeostasis as a consequence of alterations in intracellular sodium concentrations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Likewise previously reported in the MEPPC syndrome (Beckermann et al, 2014; Calloe et al, 2018; Laurent et al, 2012; Mann et al, 2012; Nair et al, 2012; ter Bekke et al, 2018; Zakrzewska‐Koperska et al, 2018), our patient presented incessant multifocal polymorphic PVCs originating from the fascicular‐Purkinje system, atrial ectopic beats, and junctional rhythm responsible for DCM and left ventricular dysfunction. Concerning the molecular mechanisms leading to DCM, we can only speculate, like others (Bezzina & Remme, 2008), on a role for altered calcium homeostasis as a consequence of alterations in intracellular sodium concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, the underlying mechanism of the Na + -current increase seems to be different in these two Na + -channelopathies, since long QT syndrome subtype 3 is mainly associated with the appearance of a persistent Na + current. To date, there are only a few reports on the MEPPC syndrome; however, an increase in the Na +window current leading to Purkinje-related PVCs seems to be the electrophysiological hallmark of this syndrome (Beckermann et al, 2014;Calloe et al, 2018;Laurent et al, 2012;Mann et al, 2012;Nair et al, 2012;ter Bekke et al, 2018), as confirmed by the present study.…”
Section: Functional Characteristics Of the Na V 15-a204e Mutationsupporting
confidence: 87%
See 2 more Smart Citations
“…The occurrence of paroxysmal AF can be a result of TBX5 gain-of-function mutations and overexpressions of Nppa, Cx40, Kcnj2 and Tbx3 genes [7]. Na v 1.5 gain-of-function mutation is proved to be associated with an increased risk of multifocal atrial and ventricular ectopies and dilated cardiomyopathy [8].…”
Section: Introductionmentioning
confidence: 99%